The Safety and Efficacy of Inspiratory Muscle Training for Patients With Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention: Study Protocol for a Randomized Controlled Trial - Liu, YuanHui; Dai, YiNing; Liu, Zhi; Zhan, HuiMin; Zhu, Manyu; Chen, XianYuan; Zhang, ShengQing; Zhang, GuoLin; Xue, Ling; Duan, ChongYang; Chen, JiYan; Guo, Lan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Uncommonly high rates of pneumonia in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) have been observed during recent years. Inspiratory muscle training (IMT) could reduce pneumonia in patients undergoing coronary artery bypass grafting and other cardiac surgeries. The relationship between IMT and AMI is unknown. Here, we describe the feasibility and potential benefit of IMT in patients at high risk for pneumonia with AMI who have undergone primary PCI. Methods: Our study is a prospective, randomized, controlled, single-center clinical trial. A total of 60 participants will be randomized into an IMT group and control group with 30 participants in each group. Participants in the IMT group will undergo training for 15 minutes per session, twice a day, from 12 h–24 h after primary PCI, until 30 days post-randomization; usual care will be provided for the control group. The primary endpoint is the change in inspiratory muscle strength, with secondary endpoints including feasibility, pneumonia, major adverse cardiovascular events, length of stay, pulmonary function tests measure, and quality of life. Discussion: Our study is designed to evaluate the feasibility of IMT and its effectiveness in reducing rates of pneumonia in participants with AMI who have undergone primary PCI.